Assessing the Impact of Climate Change on Food Security: Empirical Evidence from Shrimp Farmers in East Java, Indonesia - Fatahullah; Syauqi Agung Firmanda; Akbar (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: Climate change poses a profound and escalating threat to global food systems, particularly for small-scale aquaculture communities such as shrimp farmers in coastal regions, whose livelihoods and food security are increasingly vulnerable to environmental variability and extreme weather events. Methods: This study investigated the impact of climate change adaptation strategies on household food security in Bangil Regency, East Java, Indonesia, based on a comprehensive analysis of 1500 shrimp farmers. Using the innovative Multivariant Probit (MVP) method to identify factors influencing the decision to adopt adaptation practices. These factors include changes in the timing of clear fry dispersion, acceleration of harvest time, polyculture practices, and changes in the type of clear fry. We also employed the Ordered Probit Model to evaluate the impact of climate change adaptation on food security, as measured by the food insecurity experience score. Results: A strong positive relationship was revealed between the level of adaptation applied and the resilience of household aquaculture among shrimp farmers. This correlation shows that the more intense adaptation is implemented, the better the food security status of households. Conclusion: This study shows that climate change adaptation has a positive impact on food security. These findings underscore the need for adaptation strategies, especially for small-scale farmers, and tailored interventions to ensure food security in the face of climate change challenges.